miR-615-5p is restrictedly expressed in cirrhotic and cancerous liver tissues and its overexpression alleviates the tumorigenic effects in hepatocellular carcinoma - El Tayebi, Hend M.; Breuhahn, Kai (FEBS letters, 2012)
microRNAs aberrant behavior in heptocellular carcinoma (HCC) plays a major role in HCC pathogenesis. miR-615-5p expression has never been evaluated in HCC. We showed that miR-615-5p was preferentially expressed in HCC, cirrhotic liver tissues and HCC cell lines, but undetected in normal livers. Forced miR-615-5p expression in HCC cell lines led to significant decrease in cell growth and migration. In-silico predication revealed insulin-like growth factor-II (IGF-II) as a potential downstream target for miR-615-5p. Forcing the expression of miR-615-5p showed downregulation of IGF-II mRNA, as well as inhibition of the luciferase activity in a luciferase reporter vector harboring the IGF-II-3′UTR target sequence. miR-615-5p acts as tumor-suppressor in HCC through targeting IGF-II.
Gesehen am 27.06.2019